2019
DOI: 10.1177/0891988719835325
|View full text |Cite
|
Sign up to set email alerts
|

ERα Gene Promoter Methylation in Cognitive Function and Quality of Life of Patients With Alzheimer Disease

Abstract: Objective: Alzheimer disease (AD) has been recognized as a progressive neurodegenerative disorder. This study aims to investigate the effects of estrogen receptor α (ERα) gene promoter methylation on the cognitive function and quality of life (QOL) of patients with AD. Methods: A total of 132 patients with AD and 135 healthy individuals were recruited for this study. The DNA in the peripheral blood was extracted and treated with bisulfite; then methylation-specific polymerase chain reaction and reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…These data validate that estrogen conducts anti-inflammatory action via ERα in microglia [150]. Moreover, patients with higher ERα promoter methylation rates showed decreased ERα mRNA expression and impaired cognition [151], which implies the importance of ERα in AD. As mentioned, it is becoming more and more appreciated that infection may be one causative factor for AD.…”
Section: The Role Of Estrogen In Adsupporting
confidence: 66%
“…These data validate that estrogen conducts anti-inflammatory action via ERα in microglia [150]. Moreover, patients with higher ERα promoter methylation rates showed decreased ERα mRNA expression and impaired cognition [151], which implies the importance of ERα in AD. As mentioned, it is becoming more and more appreciated that infection may be one causative factor for AD.…”
Section: The Role Of Estrogen In Adsupporting
confidence: 66%
“…The QOL of the participants was tested with the QOL- AD scale and their cognitive abilities were assessed using both the Mini-Mental State Examination (MMSE) and the activities of daily living (ADL) tests. The methylation status and level of expression of the ERα gene were determined in the peripheral blood of 132 patients with AD and 135 healthy control subjects ( Li et al, 2019 ). This study showed that a higher level of methylation of the ERα gene promoter correlated with a decreased ERα expression and reduced cognitive abilities in AD patients ( Li et al, 2019 ).…”
Section: Estrogenic Plants and Compounds With Potential Effects Against Alzheimer's Diseasementioning
confidence: 99%
“…The methylation status and level of expression of the ERα gene were determined in the peripheral blood of 132 patients with AD and 135 healthy control subjects ( Li et al, 2019 ). This study showed that a higher level of methylation of the ERα gene promoter correlated with a decreased ERα expression and reduced cognitive abilities in AD patients ( Li et al, 2019 ). This evidence supports the view that lower estrogenic signaling correlates with cognitive impairment in AD.…”
Section: Estrogenic Plants and Compounds With Potential Effects Against Alzheimer's Diseasementioning
confidence: 99%
“…Cognitive impairment is a pronounced symptom of AD, and it gets worse as the disease progresses . MMSE is a neuropsychological examination consisting of a series of questions and cognitive tests that are commonly used to assess the cognitive impairment and degree of dementia . In our study, we evaluated the correlations of miR‐103 and miR‐107 with MMSE score in AD patients and observed that both miR‐103 and miR‐107 were positively correlated with MMSE score and negatively associated with dementia severity in AD patients, which indicated that miR‐103 and miR‐107 might attenuate the disease progression of AD.…”
Section: Discussionmentioning
confidence: 79%